2018
DOI: 10.1002/cbin.10983
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of inward rectifier potassium current ionic channel remodeling by AT1‐Calcineurin‐NFAT signaling pathway in stretch‐induced hypertrophic atrial myocytes

Abstract: Previous studies have shown that the activation of angiotensin II receptor type I (AT ) is attributed to cardiac remodeling stimulated by increased heart load, and that it is followed by the activation of the calcineurin-nuclear factor of activated T-cells (NFAT) signaling pathway. Additionally, AT has been found to be a regulator of cardiocyte ionic channel remodeling, and calcineurin-NFAT signals participate in the regulation of cardiocyte ionic channel expression. A hypothesis therefore follows that stretch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…21,5 Kir2.1 protein is encoded by the KCNJ2 gene and is closely related to the duration of atrial repolarization. 22 The study of Lammers et al 23 revealed that expression of kir2.1 is inversely correlated with the duration of repolarization: the downregulation of kir2.1 protein expression prolonged the repolarization duration. Our results suggest that the duration of atrial repolarization in subgroup R-AA was significantly longer than that in group C and subgroup R-NAA.…”
Section: Discussionmentioning
confidence: 99%
“…21,5 Kir2.1 protein is encoded by the KCNJ2 gene and is closely related to the duration of atrial repolarization. 22 The study of Lammers et al 23 revealed that expression of kir2.1 is inversely correlated with the duration of repolarization: the downregulation of kir2.1 protein expression prolonged the repolarization duration. Our results suggest that the duration of atrial repolarization in subgroup R-AA was significantly longer than that in group C and subgroup R-NAA.…”
Section: Discussionmentioning
confidence: 99%
“…For example, activation of calcium/calcineurin/NFAT signaling increases IK1 through NFATmediated downregulation of the inhibitory microRNA-26 (173,225). IK1 was also increased in stretched neonatal rat atrial cardiomyocytes, which was also associated with augmented calcineurin activity and increased levels of nuclear NFAT3, as well as increased mRNA and protein expression of Kir2.1 (226). On the other hand, long-term β-adrenoceptor stimulation reduced IKs with a corresponding decrease in mRNA and protein expression of its β-subunit KCNE1.…”
Section: Calcineurin-dependent Transcriptional Regulationmentioning
confidence: 99%